Farnesylation of the Transducin G Protein Gamma Subunit Is a Prerequisite for Its Ciliary Targeting in Rod Photoreceptors - Brooks, Celine; Murphy, Joseph; Belcastro, Marycharmain; Heller, Daniel; Kolandaivelu, Saravanan; Kisselev, Oleg; Sokolov, Maxim (Frontiers in Molecular Neuroscience, 2018)
Primary cilia are microtubule-based organelles, which protrude from the plasma membrane and receive a wide range of extracellular signals. Various cilia use G protein-coupled receptors (GPCRs) for the detection of these signals. For instance, vertebrate rod photoreceptors use their cilia (also called outer segments) as antennae detecting photons by the GPCR rhodopsin. Rhodopsin recognizes incoming light and activates its G protein, transducin, which is composed of three subunits α, β, and γ. Similar to all G protein  subunits, the transducin G1 subunit undergoes C-terminal prenylation resulting in the addition of an isoprenoid farnesyl, however the significance of this posttranslational modification is unclear. To study the role of the farnesyl group, we genetically introduced a mutant G1, which lacked the prenylation site into the retinal photoreceptors of mice. The biochemical and physiological analyses of these mice revealed that mutant G1 dimerizes with the endogenous transducin G1 subunit and that the resulting G dimers display reduced hydrophobicity. Although mutant G dimers could form a heterotrimeric G protein, they could not mediate phototransduction. This deficiency was due to a strong exclusion of non-farnesylated G complexes from the cilia (rod outer segments). Our results provide the first evidence that farnesylation is required for trafficking of G-protein  subunits to the cilium of rod photoreceptors.